Pengaruh Penerapan Model Pembelajaran CORE Berbasis Masalah Kontekstual Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Baiq Dewi Mustika Wati; Ketut Sarjana; Dwi Novitasari; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This study aims to determine the effect of applying the CORE learning model based on contextual problems on the mathematical problem-solving abilities of SMPN 1 Masbagik students in the 2022/2023 academic year. This research is a quantitative-research with a quasi-experimental research type. The population in this study were all class IX students of SMPN 1 Masbagik for the 2022/2023 academic year with a total of 286 students. The sample selection technique used purposive sampling with a sample of 62 students consisting of two classes. Data collection used the test method with 3 description questions. The instruments in this study were lesson plans, worksheets, test questions. The data analysis technique used is parametric statistics. The results of data analysis obtained 2,000. which indicates that there is a difference in the average problem-solving ability between the experimental group and the control group. An increase in the average value indicates an increase in problem-solving abilities in the experimental group caused by the treatment given, namely the contextual problem-based CORE learning model, so it can be concluded that there is an effect of applying the contextual problem-based CORE learning model on the mathematical problem-solving abilities of class IX students of SMPN 1 Masbagik.